Marketing verde: análise da revista digital de uma empresa paranaense do ramo alimentício - Santos, Ademir Rodrigo de Araujo (2024)
This dissertation analyzed the digital communication of a food company in Paraná, exploring how builds and communicates its environmental and social identity. A digital magazine of the studied company was selected, classified as an effective tool for reaching different audiences, as it reinforces the organization's identity as engaged in environmental and social issues. It was chosen because it presents an accessible and visually appealing language, making the company seek to consolidate an image of responsibility and commitment to the future. Thus, nine digital editions were chosen, published between 2022 and 2023, using the content analysis methodology associated with the use of the ECODIGITAL instrument. The research sought to reveal the discursive strategies employed to project an image of commitment to sustainable practices and social responsibility. Thus, the studied company uses its digital magazine as a strategic platform to transmit sustainability messages, promoting topics such as family farming, reduction of environmental impact, product quality and social responsibility. However, the company's communication faces the challenge of balancing the promotion of its image with the need to provide concrete data and evidence of its sustainable actions, avoiding perceptions of greenwashing. It also revealed that in some cases the superficial use of terms related to sustainability can harm the public's perception, and greater transparency is needed to prevent this communication from being perceived as greenwashing. Furthermore, it highlighted that the company studied aligns itself with the principles of Marketing 4.0, by using the digital environment to connect with its consumers in a more humanized way. However, the lack of a more concrete and detailed approach in relation to sustainable actions raises the need for greater clarity in the presentation of its results and impacts. Therefore, it is concluded that, in order to strengthen its reputation and consolidate its position as a company committed to sustainability, the company studied needs to adopt more transparent communication focused on verifiable data.